A new permopsocidan genus and species from the Late Permian of Australia (Insecta: Acercaria: Psocidiidae) - Prokop, Jakub; Garrouste, Romain; Nel, André (Zootaxa, 2016)
The psocidiid Hypopsylla belmontensis gen. et sp. nov., new psocidiid genus and species, is described and figured from the Late Permian of New South Wales in Australia. This discovery extends the knowledge on the diversity of the small order Permopsocida whose members passed the Permian-Triassic boundary and became extinct in Cretaceous.
Keywords: Austrálie; křídla zvířecí; Animals; Australia; zkameněliny; Phylogeny; Female; zvířata; hmyz; fylogeneze; Fossils; Insecta; Wings, Animal; ženské pohlaví